2001
DOI: 10.2527/2001.79111x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting percentage of intramuscular fat using two types of real-time ultrasound equipment.

Abstract: A total of 500 steers were used to develop models for prediction of percentage of intramuscular fat (PIMF) in live beef cattle. Prior to slaughter, steers were scanned across the 11th and 13th ribs using Aloka 500V and PIE scanner 200 machines. After slaughter, a cross-sectional slice of the longissimus dorsi muscle from the 12th rib facing was used for chemical extraction to determine carcass intramuscular fat measures (CIMF). Texture analysis software was used by two interpreters to define image parameters, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
1
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 11 publications
4
65
1
3
Order By: Relevance
“…Folch et al, 1957) or estimated in vivo by real-time ultrasound (e.g. Hassen et al, 2001;Newcom et al, 2002) and H 1 -NMR (e.g. Boesch et al, 1997;Toussaint et al, 2002) techniques.…”
Section: Imf and Marbling: Definition And Role In Palatability Of Meamentioning
confidence: 99%
See 1 more Smart Citation
“…Folch et al, 1957) or estimated in vivo by real-time ultrasound (e.g. Hassen et al, 2001;Newcom et al, 2002) and H 1 -NMR (e.g. Boesch et al, 1997;Toussaint et al, 2002) techniques.…”
Section: Imf and Marbling: Definition And Role In Palatability Of Meamentioning
confidence: 99%
“…As marbling score in these animals is genetically highly correlated with muscle lipid content (r G 5 0.91), selection based on the former may lead to a correlated improvement in tenderness (for review, see Hocquette et al, 2006). This relationship explains most of the efforts dedicated to the development of live scanning for IMF content as a selection tool in the United States and Australia (Reverter et al, Intramuscular fat content in meat-producing animals 2000; Hassen et al, 2001;Sapp et al, 2002). However, as marbling is positively genetically correlated to the carcass fatness, the undesirable side effects of selection on the basis of IMF content or marbling are often the increase in carcass fatness.…”
Section: Genetic and Genomic Markers Of Imf Contentmentioning
confidence: 99%
“…Sería deseable en futuros estudios evaluar el efecto que tiene tomar distintas distancias entre píxeles para comprobar cuál es la que mejor discrimina, así como combinar los distintos factores que pueden influir (variables, orientaciones, etc) y realizar un análisis discriminante que permita detectar los cambios texturales con mayor precisión (Christodoulou et al, 2003;Hassen et al, 2001;Sheppard & Shih, 2005;Michail et al, 2007). Es posible además pensar que la respuesta no sea igual en hombres que en mujeres (Gaida et al, 2004), debido a factores hormonales que puedan influir en la síntesis de coláge-no, por lo que en futuros estudios habrá que tener en cuenta esta variable.…”
Section: Discussionunclassified
“…Wilson et al (1993) and Izquierdo et al (1996) found an R 2 range from 0.44 to 0.70 for various prediction models. Hassen et al (2001) found values of R 2 ranging from 0.69 to 0.91 for various prediction models of IMF content in meat. Liu et al (1993) and Gerrard et al (1996) correlated the marbling degree detected subjectively by a group of classifi ers with the IMF content determined chemically, and found highly signifi cant correlations r=0.92 and r=0.75.…”
Section: Introductionmentioning
confidence: 99%
“…Several papers have dealt with assessing IMF content and marbling degree by ultrasound only or combined with computer image analysis (Newman, 1987;Wilson et al, 1993;Brethour, 1994;Park et al, 1994;Hassen et al, 2001). The results to date of different authors suggest that the method can also be used in practice.…”
Section: Introductionmentioning
confidence: 99%